Subsidence of uncemented short stems in reverse shoulder arthroplasty: a multicenter study - Nolte, Anna-Katharina; Lädermann, Alexandre; Wittmann, Thomas; Schnetzke, Marc; Nolte, Philip-Christian; Collin, Philippe; Raiss, Patric (Journal of Clinical Medicine, 2020)
Background: The radiological phenomenon of subsidence following the implantation of uncemented short-stem reverse prostheses (USSP) has not yet been described. The purpose of this study was to describe the rate and potential risk factors for subsidence. We hypothesized that subsidence may be a frequent finding and that a subsidence of >5 mm (mm) is associated with an inferior clinical outcome. Methods: A total of 139 patients with an average age of 73 ± 9 years were included. The clinical and radiological outcome was evaluated at a minimum follow-up (FU) of 12 months. Results: No humeral component loosening was present at a mean FU of 18 (range, 12–51) months. Mean Constant Score (CS) and Subjective Shoulder Value (SSV) improved significantly from 34.3 ± 18.0 points and 37.0 ± 19.5% preoperatively to 72.2 ± 13.4 points and 80.3 ± 16.5% at final FU (p < 0.001). The average subsidence of the USSP was 1.4 ± 3.7 mm. Subsidence of >5 mm was present in 15 patients (11%). No association between a subsidence >5 mm and CS or SSV was found (p = 0.456, p = 0.527). However, a subsidence of >5 mm resulted in lower strength at final FU (p = 0.022). Complications occurred in six cases (4.2%), and the revision rate was 3.5% (five cases). Conclusions: Although subsidence of USSP is a frequent radiographic finding it is not associated with loosening of the component or a decrease in the clinical outcome at short term FU. Level of evidence: Level 4, retrospective study.
Gesehen am 06.05.2021